Application of MAT Using Methyl Eugenol and Cue-Lure to Control Bactrocera spp. in Vegetable Centers of North Sulawesi - Maxi Lengkong; Caroulus S. Ranten; Daisy S. Kandowangko (Postgraduate, University of Mataram, 2025)
Fruit fly Bactrocera spp is one of the limiting factors in vegetable crop production. The male annihilation tehnique control method can control fruit fly populations by using sex pheromones namely Methyl eugenol and Cue-lure which are able to attract male fruit flies. The purpose of the study was to identify the types of fruit flies that attack vegetable crops, analyze the behavior of the captured population and the differences in the types of fruit flies against the use of methyl eugenol and Cue-lure. The research method is by placing traps containing methyl eugenol and cue-lure at a number of points according to the location so that it can support the representation of fruit fly distribution areas in vegetable crop centers. Observations will be carried out for 6 observations with an interval of 2 weeks. The results showed that the identification of fruit fly species caught using cue-lure a mounted to six species and methyl eugenol there were 11 species The population of fruit flies caught in the four locations of vegetable crop centers using methyl eugenol was higher in the total number of 4719 individuals with a range of 1042-1270 individuals compared to the cue-lure attractant catch of 2973 individuals with a range of 701-743 individuals.